β(2)-AR blockade potentiates MEK1/2 inhibitor effect on HNSCC by regulating the Nrf2-mediated defense mechanism - Mele, Luigi (Cell Death Dis, 2020)
The β2-Adrenergic receptor (β2-AR) is a G protein-coupled receptor (GPCR), involved in the development of many cancers, among which HNSCC. In this contest, β2-AR signaling interacts with different pathways, such as PI3K and MAPK, commonly activated by TK receptors. For this reason, TK blockade is one of the most adopted therapeutic strategies in HNSCC patients. In our study we investigated the effects of the β2-AR blocking in HNSCC cell lines, using the selective inhibitor ICI118,551 (ICI), in combination with the MAPK inhibitor U0126. We found that ICI leads to the blocking of p38 and NF-kB oncogenic pathways, strongly affecting also the ERK and PI3K pathways. Cotreatment with U0126 displays a synergic effect on cell viability and pathway alteration. Interestingly, we found that the β2-AR blockade affects Nrf2-Keap1 stability and its nuclear translocation leading to a drastic ROS increase and oxidative stress. Our results are confirmed by a TCGA dataset analysis, showing that NFE2L2 gene is commonly overexpressed in HNSC, and correlated with a lower survival rate. In our system, the PI3K pathway inhibition culminated in the blocking of pro-survival autophagy, a mechanism normally adopted by cancer cells to became less responsive to the therapies. The mTOR expression, commonly upregulated in HNSC, was reduced in patients with disease-recurrence. It is well known that mTOR has a strong autophagy inhibition effect, therefore its downregulation promoted pro-survival autophagy, with a related increase recurrence rate. Our findings highlight for the first time the key role of β2-AR and related pathway in HNSCC cell proliferation and drug resistance, proposing it as a valuable therapeutic molecular target.